2019
DOI: 10.1101/865394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetic control of PRC1 reveals that bridging fibers promote chromosome alignment by overlap length-dependent forces

Abstract: During metaphase, chromosome position at the spindle equator is mainly regulated by the forces exerted by kinetochore microtubules. However, the role of forces arising from mechanical coupling between sister kinetochore fibers and bridging fibers, whose antiparallel microtubules are crosslinked by protein regulator of cytokinesis 1 (PRC1), in chromosome alignment is unknown. Here we develop an optogenetic approach for acute removal of PRC1 and show that PRC1 promotes kinetochore alignment. PRC1 removal resulte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 81 publications
4
15
0
Order By: Relevance
“…Treatment of cells with a microtubule-destabilizing agent that results in thinner k-fibers causes a reduction of the interkinetochore tension (Dudka et al, 2018), supporting the former possibility. However, a similar effect on interkinetochore tension was observed upon perturbation of the bridging fiber by removing the microtubule crosslinker PRC1 (Jagrić et al, 2020;Kajtez et al, 2016;Polak et al, 2017), in agreement with the latter possibility. Our observation that the interkinetochore tension was most severely affected in the inner part of the spindle, where the bridging fibers were most impaired, suggests a link between interkinetochore tension and augmin-generated bridging microtubules.…”
Section: Discussionsupporting
confidence: 79%
“…Treatment of cells with a microtubule-destabilizing agent that results in thinner k-fibers causes a reduction of the interkinetochore tension (Dudka et al, 2018), supporting the former possibility. However, a similar effect on interkinetochore tension was observed upon perturbation of the bridging fiber by removing the microtubule crosslinker PRC1 (Jagrić et al, 2020;Kajtez et al, 2016;Polak et al, 2017), in agreement with the latter possibility. Our observation that the interkinetochore tension was most severely affected in the inner part of the spindle, where the bridging fibers were most impaired, suggests a link between interkinetochore tension and augmin-generated bridging microtubules.…”
Section: Discussionsupporting
confidence: 79%
“…We found that inactivation of Eg5 or depletion of Kif18A abolished the left-handed twist, with presence of right-handed twist in a subset of spindles after Kif18A depletion. Both of these motors are known to exert torque on the microtubules in vitro (Bormuth et al, 2012;Mitra et al, 2018;Yajima et al, 2008), and are found within the antiparallel overlaps of bridging microtubules in the spindle (Jagrić et al, 2020;Kajtez et al, 2016;Mann and Wadsworth, 2018). Thus, we suggest that they generate the twisted shape of the bundle by rotating the antiparallel microtubules within the bundle around each other (Fig.…”
Section: Mechanisms That Generate Spindle Twistmentioning
confidence: 73%
“…As it was previously shown, removal of the PRC1 from the spindle partially disassembles bridging fibers and affects spindle shape (Jagrić et al, 2020). Without PRC1, spindles have less curved and more diamond-like shape (Jagrić et al, 2020;Kajtez et al, 2016), which led us to hypothesize that the twist might also be affected. Surprisingly, when we depleted PRC1, the spindles had right-handed twist of 0.26 ± 0.15 °/µm (n = 14) ( Fig.…”
Section: Depletion Of Prc1 Makes the Spindles Twist In A Right-handedmentioning
confidence: 79%
See 1 more Smart Citation
“…To perturb specifically bridging fibers, we depleted PRC1 ( Fig. S1), which results in ~50% decrease of the number of microtubules in the bridging fiber without affecting the length of their antiparallel overlaps (Jagrić et al, 2020). We found that depletion of PRC1 did not change the flux velocity of bridging or kinetochore microtubules (Fig.…”
Section: Sliding Forces From the Bridging Fiber Are Transmitted Onto mentioning
confidence: 91%